PLANNING FOR IMPROVING ENVIRONMENTAL ROADS IN SUMAMPIR VILLAGE PURWOKERTO - Barkah, Atiyah; Laksono, Taufik Dwi; Wiyanti, Dwi Sri (Universitas Wijayakusuma Purwokerto, 2025)
Roads are one of the important transportation facilities in social life. The damage that occurred was in Gang Mawar Jalan Riyanto with the level of damage being quite severe, disrupting the activities of some people who usually use it. Seeing these conditions, it is necessary to plan road improvements in this activity, namely Gang Mawar, Jalan Riyanto, Sumampir Village, North Purwokerto District, Banyumas Regency. The objectives of this activity include getting the results of the planning for the repair of Alley Mawar, knowing the budget plan for carrying out the repair work on Alley Mawar and knowing the time needed to carry out the repair work on Alley Mawar I, II and V. From the measurement results, a floor plan and cross section is planned with the planned dimensions. Budget Plan The required cost is IDR. 96.614.375,- and the time required for implementation is 4 working days. Keywords: Road Pavement, Flexible Pavement, Cost Budget